(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Kaolin is a clay mineral that has found its huge use in electrical insulation. In electrical power industries, mullite insulators plays a vital role during electric power transmission. The transformation of kaolin to mullite via sintering method was carried out by varying the temperature during heating at interval of from to . The mass of the kaolin was observed to have changed during the heating until the complete transformation took place at the temperature of 11500C. The dielectric strength (breakdown voltage) was analysed by sending high input voltage through the samples and measuring the output voltage until breakdown occurred. The input voltage of to was passed through the samples and breakdown occurred at input voltage for almost all the samples. The leakage current was also determined using Ohm’s law. 11500C was found to be the optimum temperature for the transformation of kaolin to mullite. The leakage current value ( )was found to be negligible making mullite a good dielectric material for insulation.